2019
DOI: 10.1002/mrm.27879
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the diffusion time dependence of intravoxel incoherent motion in the brain

Abstract: Purpose To investigate the diffusion time (TD) dependence of intravoxel incoherent motion (IVIM) signals in the brain. Methods A 3‐compartment IVIM model was proposed to characterize 2 types of microcirculatory flows in addition to tissue water in the brain: flows that cross multiple vascular segments (pseudo‐diffusive) and flows that stay in 1 segment (ballistic) within TD. The model was first evaluated using simulated flow signals. Experimentally, flow‐compensated (FC) pulsed‐gradient spin‐echo (PGSE) and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Linear trends of the diffusivities and FA were also reported in the only other OGSE study of the in vivo human brain using a high‐performance gradient system, 13 and general positive trends of these parameters were observed in several other in vivo human OGSE studies using standard gradient strengths 4,5,23 . Moreover, the b ‐value employed in this work surpasses those used previously by a factor of at least 2, permitting diffusion tensor computation with less bias by microcirculatory flow 22,25 …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Linear trends of the diffusivities and FA were also reported in the only other OGSE study of the in vivo human brain using a high‐performance gradient system, 13 and general positive trends of these parameters were observed in several other in vivo human OGSE studies using standard gradient strengths 4,5,23 . Moreover, the b ‐value employed in this work surpasses those used previously by a factor of at least 2, permitting diffusion tensor computation with less bias by microcirculatory flow 22,25 …”
Section: Resultssupporting
confidence: 70%
“…Appearance of the non‐zero first moment might modify the contribution of the capillary blood flow to the signal attenuation observed with proposed OGSE shapes. However, due to the high b ‐values used in this work, the capillary contribution should be fully attenuated by the oscillating gradient component, 22 so the additional attenuation introduced by the first moment should play a negligible role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The concept of the two microcirculatory components were also used in studies by Le Bihan et al and Maki et al 25,26 It has been suggested that two or more changes in capillary segments are required for the diffusive limit to be valid, 27 and the satisfaction of this requirement is dependent on the microvasculature, flow velocity, and effective diffusion-time within which the diffusion is captured. 28 The conventional IVIM protocol uses monopolar or double-refocused diffusion sensitization gradients that are non-flow compensated (NC), and the measured IVIM signals contain both diffusive and ballistic microcirculatory flows. IVIM encoded with flowcompensated (FC) gradient is insensitive to ballistic flow because the water molecules, moving at a constant velocity, get rephased; therefore, this method is useful to separate diffusion and flow effects.…”
Section: Introductionmentioning
confidence: 99%
“…The IVIM signals can be modeled with three components, including the tissue water, the microcirculatory flow that passes through multiple capillary segments or the so‐called diffusive flow, and the microcirculatory flow that remains in only a few capillary segments or the so‐called ballistic flow 24 . The concept of the two microcirculatory components were also used in studies by Le Bihan et al and Maki et al 25,26 It has been suggested that two or more changes in capillary segments are required for the diffusive limit to be valid, 27 and the satisfaction of this requirement is dependent on the microvasculature, flow velocity, and effective diffusion‐time within which the diffusion is captured 28 . The conventional IVIM protocol uses monopolar or double‐refocused diffusion sensitization gradients that are non‐flow compensated (NC), and the measured IVIM signals contain both diffusive and ballistic microcirculatory flows.…”
Section: Introductionmentioning
confidence: 99%